A long‐term perspective on entrepreneurial strategies and their impact on British road policy. (27th September 2019) - Witting, Antje; Dudley, Geoffrey
Abstract: The case study presented in this paper combines citation and discourse network analyses to explore entrepreneurial strategies and their long‐term impact on public policy. The analysis draws on and develops previously published research that documents entrepreneurial influences on British road policy since the 1980s. Drawing in particular upon evidence presented in the 2013 Action for Roads White Paper, we conclude that it is not enough to focus research on a policy entrepreneur's capacity to mobilize a majority for policy change through skillful leadership and the strategic use of expertise and social capital to gain the expected benefits. Studies must also take into account the fact that once influential individuals may still impact legislation in an advisory capacity by focusing resources on a particular arena. More importantly, this strategy can, in the long term, explain why British road policy tends to remain relatively stable. 摘要: 本文中的案例研究结合引文和话语网络分析，探究企业家策略及策略对公共政策产生的长期影响。以往发表的研究记录了自1980年以来企业家策略对英国公路政策产生的影响，本文则利用该研究加以发展。笔者特别利用2013年公路行动白皮书中展示的相关证据并作出结论，认为研究仅聚焦于政策企业家在通过专业领导力动员大多数人支持政策变化一事上的能力，策略性运用专业技能和社会资本以获取所期望的利益，是不足的。研究必须同时考量一个事实，即那些曾经极具影响力的个人可能以顾问身份通过将资源聚焦于特定领域，进而影响立法。更重要的是，这一策略能从长期的角度解释为何英国公路政策往往保持相对稳定。 Resumen: El estudio de caso presentado en este documento combina el análisis de redes de citas y discursos para explorar estrategias empresariales y su impacto a largo plazo en las políticas públicas. El análisis se basa en y desarrolla una investigación previamente publicada que documenta las influencias empresariales en la política vial británica desde los años ochenta. Partiendo específicamente de la evidencia presentada en el Libro Blanco de Action for Roads 2013, llegamos a la conclusión de que no es suficiente centrar la investigación en la capacidad de un empresario de políticas para movilizar a una mayoría para el cambio de políticas a través de un liderazgo hábil y el uso estratégico de la experiencia y el capital social para obtener los beneficios esperados. Los estudios también deben tener en cuenta el hecho de que, una vez que las personas influyentes pueden tener un impacto en la legislación a título de consultores, concentran los recursos en un ámbito particular. Más importante aún, esta estrategia puede, a largo plazo, explicar por qué la política vial británica tiende a permanecer relativamente estable.